2018
DOI: 10.1093/database/bay117
|View full text |Cite
|
Sign up to set email alerts
|

GCDB: a glaucomatous chemogenomics database forin silicodrug discovery

Abstract: Glaucoma is a group of neurodegenerative diseases that can cause irreversible blindness. The current medications, which mainly reduce intraocular pressure to slow the progression of disease, may have local and systemic side effects. Recently, medications with possible neuroprotective effects have attracted much attention. To assist in the identification of new glaucoma drugs, we created a glaucomatous chemogenomics database (GCDB; http://cadd.pharmacy.nankai.edu.cn/gcdb/home) in which various glaucoma-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We applied SVM-RFE as the first step feature selection and obtain 11 features. As reported that SVM-RFE usually provides a criterion to rank features based on their relevancy and complementarity but does not take the redundancy among features into account [ 16 ], we therefore implemented the second step to remove potential redundant features of high correlations. We calculated the Pearson correlation coefficients among 11 features and removed potential redundant features with a threshold of 0.65.…”
Section: Resultsmentioning
confidence: 99%
“…We applied SVM-RFE as the first step feature selection and obtain 11 features. As reported that SVM-RFE usually provides a criterion to rank features based on their relevancy and complementarity but does not take the redundancy among features into account [ 16 ], we therefore implemented the second step to remove potential redundant features of high correlations. We calculated the Pearson correlation coefficients among 11 features and removed potential redundant features with a threshold of 0.65.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cellular pathways and environment and the biological functions and processes affected by the chemicals are systematically explored. Such system-level analyses (Bian et al 2019; Pei et al 2017, 2019; Wei et al 2018; Wu et al 2019; Xu et al 2016) assist in deciphering polypharmacological effects and disease mechanisms (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%